2021
DOI: 10.1080/03004430.2021.1877284
|View full text |Cite
|
Sign up to set email alerts
|

Children’s family drawings: association with attachment representations in story stem narratives and social and emotional difficulties

Abstract: We examined representations of attachment security using story stem narratives (Manchester Attachment Story Task, MCAST) and a family drawing task in 50 Greek children between 4 and 6 years old. Additionally, we examined the association between attachment classification based on the family drawing task and maternal reports of social and emotional symptoms assessed using the Strengths and Difficulties Questionnaire. Attachment security classification based on the MCAST was not significantly associated with atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Concerning the concurrent validity, studies in different populations of children (i.e., community, clinical, adopted, etc. ) showed the attachment-based FD results partially converged with those of the gold-standard SSP and the Manchester Child Attachment Story Task (MCAST; Goldwyn et al, 2000), a completion task used to assess attachment representations in 4-8 years old children and rated both through four ABCD classifications and 1-to 9-point scales (Jin et al, 2018;Pace et al, 2020;Kallitsoglou et al, 2021).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Concerning the concurrent validity, studies in different populations of children (i.e., community, clinical, adopted, etc. ) showed the attachment-based FD results partially converged with those of the gold-standard SSP and the Manchester Child Attachment Story Task (MCAST; Goldwyn et al, 2000), a completion task used to assess attachment representations in 4-8 years old children and rated both through four ABCD classifications and 1-to 9-point scales (Jin et al, 2018;Pace et al, 2020;Kallitsoglou et al, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…Specifically, Jin et al (2018) suggested convergence in both classifications and scales of community and (especially) clinical children. Pace et al (2020) reported convergence of more scales in communities than in at-risk children, and Kallitsoglou et al (2021) suggested no convergence of scales among the communities. Overall, these results are too heterogeneous to assume that FD can be as trustable as other more validated attachment measures in assessing attachment, and further studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our research would allow us to discover the wealth of information contained in children’s works in greater depth. Our methodology could be applied to examine psychological and emotional traits measured through questionnaire ( Kallitsoglou et al, 2021 ) or direct observation ( Shiakou, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major uses of drawing is as a tool for assessing the psychological and relational wellbeing of children and adolescents. In clinical and legal settings, the Family Drawing test is among the most widely used projective tests for assessing the quality of a child's family relationships with a scoring system for assessing attachment (Kallitsoglou et al, 2022 ). In their opinion paper, Pace et al discussed the strengths and weaknesses of the Family Drawing test with such an attachment-based coding system.…”
Section: Drawing As a Tool For Investigating Children's Emotional Exp...mentioning
confidence: 99%